Wind Turbine Tower Optimization under Various Requirements by Using Genetic Algorithm - Yıldırım, Serdar; Özkol, İbrahim (Scientific Research Publishing, Inc., 2010)
The purpose of this study is to optimize the mass of 1.5 MW wind turbine steel tower performing Genetic Algorithm method (GA). In accordance with ASCE 7-98, AISC-89 and IEC61400-1 , the impact of loads on tower is calculated within the highest safety conditions against buckling strength of each sections of tower by means of GA codes. The stifness along tower is ensured entirely while the mass of tower is mitigated and optimized.